Design of a sunscreen considering the valorization of agroindustrial waste from the wine industry - Carrillo-Quezada, M.; Pariona-la Torre, L.; Cárdenas-Toro, F.; Nakama-Hokamura, K. (Latin American and Caribbean Consortium of Engineering Institutions, 2019)
In the present work, a design of a cosmetic product, a sunscreen SPF 50+, was proposed using ingredients obtained from wine industry residues, such as, oil from the grape seed and extract from the grape skin. . The product design begins with the study of the consumer profile, brand preference in the market, attributes most valued in the sunscreen and preference of product size. Then, from this information, a sunscreen is designed that meets the characteristics desired by the consumer, which includes the development of a standard formulation, the physicochemical characteristics and material balance for an estimated pilot production of 100 kg.
Keywords: Wine; Waste management; Pulp and paper industry; Process engineering; Environmental science; Business; Biochemical engineering; Manufacturing engineering; Chemistry; Engineering; Food science; https://purl.org/pe-repo/ocde/ford#2.11.01